Regenerative Endodontics and the promise beyond dental pulp disease repair. - Haidar, Ziyad (Journal of Oral Research, 2020)
The dental pulp is a multi-structural soft tissue composed of fibroblasts, odontoblasts, lymphocytes, endothelial cells, amongst others; with prominent formative, sensorial, and protective functions. Pulpitis is a painful inflammatory (necrotic) disease caused by untreated dental decay/caries, trauma and multiple restorations; often irreversible/ unrecoverable, due to insufficient vascularization, mainly because of the anatomy of the pulp chamber: a small root canal in volume and a narrow apical foramen